Pengaruh Takaran Pupuk Kandang Ayam dan Frekuensi Pemberian Pupuk Urea Terhadap Pertumbuhan dan Hasil Tanaman Jagung (Zea mays L.) - Teddy, Teddy Syah Putra; Purwanti, Setyastuti; Suryanti, Sri (Universitas Wiralodra, 2024)
Low productivity of corn can be overcome by using fertilizer regularly. Regular fertilization has several benefits, including increasing production and yield quality. Fertilization is divided into organic fertilizers and inorganic fertilizers. Organic fertilizers are fertilizers composed of biological material, one of which is chicken manure. Inorganic fertilizers are fertilizers designed by the fertilizer industry by mixing several high-value inorganic chemicals, one of which is urea. The objectives of research to decide the right combination of doses of chicken manure and frequency of application of urea fertilizer to obtain optimal growth and yield of corn plants. The research was conducted at INSTIPER KP2, Maguwoharjo Village, Depok District, Sleman Regency, Yogyakarta, from August to November 2022. The research design used was factorial which consisted of two factors and organized in a completely randomized design (CRD) with three replications. The first factor was the dose of chicken manure which consisted of three levels, namely control, 87 gram and 174 gram. The second factor was the frequency of application of urea fertilizer which consists of three levels, namely two times fertilization, three times fertilization and four times fertilization. Research data were analysis of variance (Anova) at a significant level of 5%. The research result showed that there was a significant interaction among the application of chicken manure 174 gram and the frequency of application of urea fertilizer four times the fertilization on the parameters of plant height and leaf area. The dose of chicken manure 174 gram significantly increased the growth parameters of plant dry weight and yield parameters of cob weight, cob diameter, weight of 100 large seeds and seed weight. The frequency of application of urea fertilizer four times of fertilization significantly increased the growth parameters of plant dry weight and yield parameters of cob weight, cob diameter, weight of 100 large seeds and seed weight.